Non-cognitive Characteristics of Gifted Students With Learning Disabilities: An In-depth Systematic Review - Beckmann, Else; Minnaert, Alexander (Frontiers in Psychology, 2018)
Gifted students who also have learning disabilities (G/LD) are often overlooked when students are assessed either for giftedness or specific learning disabilities. The cognitive and noncognitive characteristics of these G/LD students are habitually discussed only briefly alongside identification and intervention issues and, beyond that, the relevance of noncognitive characteristics is often left unconsidered. Accordingly, this study aims to conduct an in-depth review of the noncognitive characteristics of these students for identification and intervention purposes. Detailed analysis was performed on 23 publications. High levels of negative emotions, low self-perception and adverse interpersonal relationships, as well as high levels of motivation, coping skills and perseverance were found among these students. A common characteristic was a high degree of frustration with the academic situation. The study reveals that these students show considerably duality in their noncognitive characteristics which requires tailored counselling skills to provide effective support for their learning needs.